Atorvastatin and simvastatin in clinical management of high-risk patients - S. A. Shalnova; A. D. Deev (Кардиоваскулярная терапия и профилактика, 2009)
Aim. То assess the use of average therapeutic doses of atorvastatin and simvastatin (Torvacard and Simvacard) in real-world clinical management of high-risk patients.Material and methods. The study included 347 doctors from 30 Russian cities and 1163 high-risk patients randomised into two groups: Torvacard, 20 mg/day (n=672) and Simvacard, 20 mg/day (n=491). Ah patients completed a standard questionnaire, underwent anthropometry and measurement of blood pressure, heart rate, total cholesterol (TCH), low and high-density lipoprotein CH(LDL-CH, HDL-CH), triglycerides (TG), as well as liver enzymes and creatine phosphokinase activity as safety markers. The study lasted for 3 months. Lipid-lowering therapy was regarded as effective if target TDT-CH levels (<2,5 mmol/1) were achieved.Results. TCH and LDL-CH levels reduced by 31,2% and 38,8%, respectively, in Torvacard group, and by 21,4% and 21,5% in Simvacard group (p<0,001). Both medications significantly reduced TG levels — by 21,1% and 15,9%, respectively. In Torvacard group, more than 50% of the patients achieved target LDL-CH levels, and in Simvacard group — only 19,6% (p<0,0001). In total, 18 adverse events were registered: 10 (1,5%) and 8 (1,5%) in Torvacard and Simvacard groups, respectively (p=0,9).Conclusion. Early administration of a higher Torvacard dose (20 mg) was much more effective in achieving target lipid levels in high-risk patients, without increasing adverse event risk. Clinicians should remember about the positive correlation between statin dose and adverse effect risk, monitoring chnical and laboratory safety parameters.